'Google it!' Forecasting the US unemployment rate with a Google job search index - Francesco D'Amuri; Juri Marcucci (University of Essex, Institute for Social and Economic Research (ISER), 2009)
We suggest the use of an Internet job-search indicator (the Google Index, GI) as the best leading indicator to predict the US unemployment rate. We perform a deep out-of-sample forecasting comparison analyzing many models that adopt both our preferred leading indicator (GI), the more standard initial claims or combinations of both. We find that models augmented with the GI outperform the traditional ones in predicting the monthly unemployment rate, even in most state-level forecasts and in comparison with the Survey of Professional Forecasters.
Keywords: 330